2013
DOI: 10.1371/journal.pone.0069682
|View full text |Cite
|
Sign up to set email alerts
|

Undernutrition Affects Cell Survival, Oxidative Stress, Ca2+ Handling and Signaling Pathways in Vas Deferens, Crippling Reproductive Capacity

Abstract: BackgroundThe aim of this work was to investigate the mechanisms by which chronic malnutrition (CM) affects vas deferens function, leading to compromised reproductive capacity. Previous studies have shown that maternal malnutrition affects the reproductive tracts of adult male offspring. However, little is known about the effects of CM, a widespread life-long condition that persists from conception throughout growth to adult life.Methodology/Principal FindingsYoung adult male rats, which were chronically malno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 38 publications
2
38
2
Order By: Relevance
“…In previous studies [30], doxorubicin significantly induced ROS production and impaired cardiomyocyte viability. Indeed, reduced ROS production prompted survival of a variety of cell types [31]. In the present study, HUA stimulated ROS formation, thereby impairing H9c2 cardiomyocyte viability.…”
Section: Discussionsupporting
confidence: 47%
“…In previous studies [30], doxorubicin significantly induced ROS production and impaired cardiomyocyte viability. Indeed, reduced ROS production prompted survival of a variety of cell types [31]. In the present study, HUA stimulated ROS formation, thereby impairing H9c2 cardiomyocyte viability.…”
Section: Discussionsupporting
confidence: 47%
“…The ingredients were (in g%): beans 18, manioc flour 65, jerked meat 4, and sweet potatoes 13 [23]. Full details regarding diet preparation are given elsewhere [5,24]. The control diet (a commercial chow from Purina Agribands, Paulinia, Brazil) met the recommendations of the American Institute of Nutrition for rodents (AIN-93G) [25].…”
Section: Diet and Animal Groupsmentioning
confidence: 99%
“…During the development of secondary follicle, however, not all secondary follicles reach maturation and some may be subject to loss or attrition caused by internal and external factors. Studies in Merino sheep showed that the initiation and maturation of secondary follicles during fetal life and early postnatal period were inhibited by malnutrition, this may be attributed to the reactive oxygen species (ROS) production and oxidative stress induced by malnutrition . In addition, studies on Merino sheep showed that secondary follicle development during fetal and early postnatal period under normal conditions was suppressed by plasma cortisol, a stress‐related hormone that was reported to induce ROS production and oxidative stress …”
Section: Introductionmentioning
confidence: 99%